2005
DOI: 10.1007/s00424-005-1476-5
|View full text |Cite
|
Sign up to set email alerts
|

No correlation between the p38 MAPK pathway and the contractile dysfunction in diabetic cardiomyocytes

Abstract: Besides the classical cardiovascular diseases, high levels of blood glucose directly interfere with cardiomyocytes. The mechanisms responsible for this have not yet been explored in detail. This study aims to determine if hyperglycaemia has any impact on prominent signalling molecules and on the contractile function of cardiomyocytes. Freshly isolated cardiomyocytes from adult rats were treated with various concentrations of glucose. Formed free radicals were measured by DCF-fluorescence. TGFbeta expression an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 30 publications
1
7
0
Order By: Relevance
“…[2][3][4][5][6][7][8] The expression and activation of MAPKs are also altered in the setting of hyperglycemia and diabetes in several animal models. [9][10][11][12][13][14] Recent studies in our laboratory demonstrated that PKC-alpha and PKC-beta are upregulated and activated in the human diabetic (type 2) myocardium in the setting of CP/CPB. [15][16][17][18][19][20][21] Whether diabetes, particularly if combining with CP/CPB and cardiac surgery, further affects MAPKs signaling in the human myocardium has not been investigated.…”
mentioning
confidence: 99%
“…[2][3][4][5][6][7][8] The expression and activation of MAPKs are also altered in the setting of hyperglycemia and diabetes in several animal models. [9][10][11][12][13][14] Recent studies in our laboratory demonstrated that PKC-alpha and PKC-beta are upregulated and activated in the human diabetic (type 2) myocardium in the setting of CP/CPB. [15][16][17][18][19][20][21] Whether diabetes, particularly if combining with CP/CPB and cardiac surgery, further affects MAPKs signaling in the human myocardium has not been investigated.…”
mentioning
confidence: 99%
“…In the past, a focus has been set on the reformation of sarcomeres, while the initiation of this process, namely the degradation of existing sarcomeres, has achieved less attention. We have previously shown that during the cultivation process, an increased expression of p38 MAP kinase occurs [ 31 ]. Activation of p38 MAP kinase drives embryonic stem cells into cardiomyocyte-specific differentiation by enhancing the transcription of myocyte enhancer factor 2C, a transcription factor required for cell differentiation [ 32 , 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…Cell contraction was analyzed as described previously using a cell‐edge detection system at a frequency of 0.5 Hz (Wenzel et al, ). Cells were incubated for 24 h with (1) pure and conditioned medium from human, murine, and rat CDCs, (2) with Il‑6 (100 pg/ml, 1 ng/ml, 10 ng/ml, 100 ng/ml, or 1 μg/ml) (3) with pure and conditioned media from human CDCs derived from both a hypertensive and a normotensive donor and a specific antibody against Il‑6 in a dilution of 1/400 as recommended by the manufacturer in the product’s datasheet (Abcam®, Cambridge, UK, rabbit polyclonal) (4) the antibody alone and (5) pure and conditioned media from Il‑6 −/− and Il‑6 +/+ mice.…”
Section: Methodsmentioning
confidence: 99%